A survey of instructional needs of primary school teachers in Nigeria (2004)
The study sought to establish profiles of perceived instructional needs of teachers in Nigerian primary schools and to ascertain whether there is any group difference in the perceived needs based on gender and class taught. It made use of750primary school teachers (210 males and 540 females) from 12 states of Nigeria including Abuja. The subjects responded to a 27-item questionnaire. The questionnaire contains a set of items on instructional practices based on a three-point Likert-type scale of which the respondents indicated the level of their needs. Data analysis involved the use of percentages and chi-square statistics. The results showed that a number of perceived instructional needs are common to most teachers in the Nigerian primary schools. The study also revealed that there is no group difference in the teachers ' instructional needs based on gender but that a group difference exists in the teachers 'needs based on whether or not the teacher teaches lower or higher class. The implications of the findings on primary school teacher training and in-service programme in Nigeria were discussed.